Operando and Time-Resolved X-Ray Absorption Spectroscopy for the Study of Photoelectrode Architectures. (20th July 2016) - Baran, Tomasz; Fracchia, Martina; Vertova, Alberto; Achilli, Elisabetta; Naldoni, Alberto; Malara, Francesco; Rossi, Giacomo; Rondinini, Sandra; Ghigna, Paolo; Minguzzi, Alessandro; D'Acapito, Francesco
Graphical abstract: Highlights: Time resolved XAS is introduced for the study of photoelectrodes. Pump & Probe: UV–vis pulses are synchronized with synchrotron bunches. The method is effectively tested onto a α-Fe2 O3 /IrOx photoanode architecture. The dynamics of charge transfer between the layers can be investigated. Abstract: Photoelectrocatalytic processes (e.g. water splitting) are particularly interesting as a method of solar to chemical energy conversion. The catalytic process is driven by transient changes in the semiconductor material's properties, such as the metal oxidation state, the local reconstruction of catalytic sites or charge recombination processes. Here, we report a novel experimental technique for performing pump and probe time-resolved hard X-ray absorption spectroscopy in electrochemical conditions under UV–vis irradiation: pump and probe XAS enables the study of processes occurring in pico- to microseconds time scale by probing the local electronic properties of a selected atom. The described technique was developed using α-Fe2 O3 /IrOx as a model photoelectrode.